Conjugate heat transfer analysis of laser-irradiated cylindrical-shaped biological tissue embedded with the optical inhomogeneity. (October 2022) - Kishore, Pankaj; Kumar, Sumit; Patel, Vipul M.
Abstract: The current study is associated with the numerical investigation of the thermal behavior of cylindrical-shaped biological tissue during laser-based photo-thermal therapy. The light-tissue interaction has been modeled using the transient radiative transfer equation (TRTE). The TRTE in a cylindrical coordinate system is solved using the modified discrete ordinate method to obtain the intensity distribution inside the biological tissue. The solution of TRTE is coupled with Pennes bio-heat transfer equation (BHTE) to understand the thermic response of biological tissue. The Pennes BHTE is solved using the finite volume method (FVM). The two different types of optical inhomogeneity (absorption and scattering inhomogeneity) are considered in the current study. The inhomogeneity's optical and thermophysical properties may be the same/different from the homogeneous biological tissue. This conjugate heat transfer problem (CHTP) is solved using the harmonic mean technique. First, the present result is verified with the data available in the literature. Subsequently, the effect of inhomogeneity's optical properties on the temperature distribution is investigated. A comparative study between the same and different thermophysical properties of the biological tissue and inhomogeneity is performed. This study will help to accurately model the thermal characteristics of the laser-irradiated biological tissue having different thermophysical properties than the inhomogeneity.